2005
DOI: 10.1152/jn.00513.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity for the Human Body in the Fusiform Gyrus

Abstract: Functional neuroimaging studies have revealed human brain regions, notably in the fusiform gyrus, that respond selectively to images of faces as opposed to other kinds of objects. Here we use fMRI to show that the mid-fusiform gyrus responds with nearly the same level of selectivity to images of human bodies without faces, relative to tools and scenes. In a group-average analysis (n = 22), the fusiform activations identified by contrasting faces versus tools and bodies versus tools are very similar. Analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
480
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(530 citation statements)
references
References 34 publications
46
480
3
1
Order By: Relevance
“…Tsao and colleagues (22) have proposed in a related monkey fMRI study that the face area in the posterior STS may be homologous to the human FFA. However, the human FFA has been shown to respond differentially to faces and human bodies (39), whereas the pFace area that we identified in the macaque did not discriminate monkey faces and body parts.…”
Section: Discussioncontrasting
confidence: 73%
“…Tsao and colleagues (22) have proposed in a related monkey fMRI study that the face area in the posterior STS may be homologous to the human FFA. However, the human FFA has been shown to respond differentially to faces and human bodies (39), whereas the pFace area that we identified in the macaque did not discriminate monkey faces and body parts.…”
Section: Discussioncontrasting
confidence: 73%
“…As expected, given the part -whole relation between bodies and faces, the results showed that the middle part of the FG, which is typically associated with the perception of facial identity, is more activated for bodies than for faces (van de Riet et al 2009). Previous studies have shown that there was partial overlap between the face-selective and body-selective region within the FG (Hadjikhani & de Gelder 2003;Peelen & Downing 2005). In fact, viewing whole-body expressions elicited a wider network of brain areas compared with faces, including other areas previously associated with perception of facial expressions, such as STS.…”
Section: Investigations Of Bodies Will Extend the Scope Of Face-basedsupporting
confidence: 81%
“…Third, the 'FFA' was defined as a large square ROI, over a centimetre on a side, a method that guarantees the inclusion of voxels neighbouring but not in the FFA. Thus, it is possible, for example, that any training effects on Greebles may arise from the body-selective 'fusiform body area' (FBA; Peelen & Downing 2005;Schwarzlose et al 2005) which is adjacent to the FFA (see §3e) rather than from the FFA itself. Finally, 'activation' was defined as the sum across the 64 voxels in the ROI of t-values resulting from a comparison of upright to inverted responses within each voxel (after excluding all t-values less than 0.1).…”
Section: Evidence From Fmri: Functional Specificity Of the Ffamentioning
confidence: 99%